Agrohidronegócio da carcinicultura: reconfigurações Ambientais, sociais e tecnológicas no município de Jaguaruana-Ceará - Silva, Janne Kleia da (Universidade Federal Rural do Semi-Árido, 2014)
The State of Ceará after the 1990s, is now inserted in front of the Agrohidronegócio expansion through construction of a developmental project characterized by a set of structural and administrative measures for modernizing character of this agricultural capital by way of large state incentives entered in some parts of the territory of Ceará, erupting in 2003 in the Vale do Jaguaribe shrimp farming that gave rise to this research guiding question: what are the main changes occurred in the social, environmental and technological aspects in Jaguaruana- CE from the sociorestructuring produced by Agrohidronegócio the Shrimp? As the main objective of this research we proposes to analyze the socio restructuring produced in the municipality of Jaguaruana due to the expansion of the Agrohidronégocio Shrimp. Secondarily search: Display contextual way socio-spatial restructuring that allowed the expansion of shrimp farming Agrohidronégocio through the state tool; Identify the environmental, technological and social aspects that after 2003 promoted a reconfiguration Jaguaruana-CE; Understand how the subjects of communities, businesses and the government interpret / interact / coexist with the impacts of shrimp aquaculture. The research method used was the dialectical.The chosen techniques for the data collection were bibliographic, documentary research and semistructured interviews. The survey results showed that Agrohidronegócio shrimp farming has been widespread in Jaguaruana-CE without effective inspections, with government incentives and significant impacts on environmental, technological and social spheres, through the shortage of family farming, the process of deterritorialization, the rural exodus, unemployment, income concentration, the risks to human and animal health through the release of effluents into water and conflicts over water bodies felt mainly by peasant populations
Agrohidronegócio of shrimp - environmental, social and Technologyreconfigurations in the municipality of Jaguaruana-Ceará
Keywords: Shrimp aquaculture; Agrohidronegócio; Jaguaribe Valley; Jaguaruana-EC; Environmental impacts - shrimp; Carcinicultura; Agrohidronegócio; Vale do Jaguaribe; Jaguaruana-CE; Impactos ambientais - carcinicultura; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE